‘It is nice that you want to improve this comic book together with us.’ The letters page’s significance in the transnational adaptation of Marvel comics in Finland - Laura Antola (United Kingdom, 2022)
This article explores the transnational adaptation of Marvel’s superhero comics through an analysis of letters pages in Finnish Marvel comic books. While media products and their fan cultures have become increasingly global, analyzing the national sites for fannish activity offers new insight into the roles of local agents in transnational adaptation processes. The letters pages in Finnish Marvel comics were a site where editorial choices were legitimized, gaps in the storylines were filled and the national Marvel fandom was born. Emphasizing the role of communication between the producers and the consumers, the article brings a new perspective to the local production process of global media products.